INTEGRASI MODEL BCG: STRATEGI INOVATIF DALAM PENGELOLAAN PENDIDIKAN ISLAM RAMAH LINGKUNGAN - Hananah; Supriyono, Bangbang (CV. Jendela Gagasan, 2025)
The rapid global changes have increased the urgency of integrating environmental awareness into the management of Islamic education, considering its role in shaping an ecologically conscious generation. However, many Islamic educational institutions still face challenges in implementing structured eco-friendly strategies. This study aims to explore the potential application of the Boston Consulting Group (BCG) model as an innovative strategy in managing environment-based Islamic education. The research employs a qualitative approach with a literature review method, utilizing relevant literature to analyze the concepts and implementation of the BCG model. The findings indicate that the BCG model provides a systematic framework for categorizing educational programs into four strategic categories: Stars, Cash Cows, Question Marks, and Dogs. When applied appropriately, this model can enhance resource allocation efficiency, support the sustainability of flagship programs, and promote innovations that align with the ecological vision of Islamic education. The integration of the BCG model not only serves as a strategic solution but also a concrete step toward sustainable management of Islamic education.